Disain Aplikasi Sistem Informasi Geografi Panduan Lokasi Perkebunan Kelapa Sawit Berbasis Mobile - Erick Fernando; Surjandy Surjandy; Dina Fitria Murad (Teknik Informatika, 2019)
The development of the world of oil palm plantations in the Jambi region is so rapid and one of them is the Bahar River region. With this development, so many plantations have resulted in not all people being aware of the location or information, due to the lack of available information about the location of the area, and the distance to the location of the Oil Palm Plantation is still not clear. From the problems that occur, this study aims to make new innovations in the form of applications. A mobile-based (android) application that can provide solutions to the public so they can easily find out the location and distance they can get from where they are to get to the oil palm plantations they want that are not limited to time and place. This application development uses the waterfall approach and uses the Android programming language to build mobile applications. This research produces a mobile application that can be accessed with an Android smartphone that has been tested by the environment. Testing applications with a black box approach that gives results that the application can run according to the functions of each menu in the application so that the application is suitable for use by the user.